2006
DOI: 10.3201/eid1205.050854
|View full text |Cite
|
Sign up to set email alerts
|

Web-based Surveillance and GlobalSalmonellaDistribution, 2000–2002

Abstract: Surveillance improves control of Salmonella infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
199
7
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(220 citation statements)
references
References 13 publications
7
199
7
7
Order By: Relevance
“…In the last 20 years, S. Enteritidis has been the most frequently isolated Salmonella serotype within Europe, where it has been attributed to 85% of salmonellosis cases identified (21). This study found Shigella in 3% of patients, which was lower than the 10.8% reported in another study (22,23).…”
Section: Discussioncontrasting
confidence: 62%
“…In the last 20 years, S. Enteritidis has been the most frequently isolated Salmonella serotype within Europe, where it has been attributed to 85% of salmonellosis cases identified (21). This study found Shigella in 3% of patients, which was lower than the 10.8% reported in another study (22,23).…”
Section: Discussioncontrasting
confidence: 62%
“…Salmonella species are considered to be among the most important foodborne pathogens in the world and salmonellosis is still one of the most widespread foodborne bacterial illnesses in humans, with clinical manifestations ranging from asymptomatic state to severe disease [2]. The majority of infections are associated with the ingestion of contaminated foods such as poultry, beef, pork, eggs, milk, cheese, seafood, fruits, juices, and vegetables [3,4], although most infections caused by multidrugresistant Salmonella are acquired through contaminated foods of animal origin.…”
Section: Introductionmentioning
confidence: 99%
“…Geographical and temporal variations have been observed, but worldwide S. Enteritidis (65%) and S. Typhimurium (12%) have been considered the most common serotypes (7,10,11,13,14,17) . In agreement with these reports, four out of five isolates were serotyped as S. Typhimurium (three) and S. Enteritidis (one).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these reports, four out of five isolates were serotyped as S. Typhimurium (three) and S. Enteritidis (one). For Latin America the dominance of S. Enteritidis (31%) has been reported (13) . Patients with salmonellosis usually develop nausea, vomiting, abdominal cramping, diarrhea, and fever.…”
Section: Discussionmentioning
confidence: 99%